Ultra‑Diluted Gelsemium Sempervirens a Known Dna Topoiso‑ merase i (Top i) Inhibitor Exerts Protective Action Against Sars‑Cov‑ 2 Rbd Induced Cytokine Dysregulation - Paira, Krishnendu; Chatterjee, Debasmita; Ghosh, Sayak; Goswami, Pritam; Das, Satadal (Trends in Immunotherapy, 2025)
Gelsemium sempervirens (GS) extract is being used in phytomedicine and homeopathy for its anxiolytic properties but its mechanism of action is yet to be understood. Evidence from rodent models suggests existence of its high sensitivity to the central nervous system even in ultra‑diluted conditions. The diverse effects of its extract and/or its main alkaloids‑gelsemine, sempervirine, and koumine have been shown through different experiments in recent years. Sempervirine intercalates with DNA and inhibits topoisomerase‑I activity, which is thought to be a potential target for restricting viral replication during SARS‑CoV‑2 pathogenesis. Delta SARS‑CoV‑2 spike RBD, the recombinant protein, was procured from Abclonal Pvt. Ltd. 14th‑day‑old Gallus gallus domesticus embryos were inoculated with RBD protein along with control alcohol in pre‑ and post‑treatment sets and challenged with Gelsemium 6CH, 30CH and 200CH potencies. After 48h, allantoic ϐluids were collected during harvesting and stored at −20 ℃ for the study of different cytokine gene expressions by RT‑PCR (Reverse Transcription Polymerase Chain Reaction). GS at 6CH, 30CH, and 200CH dilutions showed up‑regulation of IFN‑α and IL‑10 gene expressions in all experimental sets. Tendencies of down‑regulation of the genes were seen with TGF‑β1, IL‑1β, and IL‑6 cytokines, with few exceptions. IFN‑β and IL‑1β gene expression changes were relatively mild and mostly inconclusive. All expressions indicate a possible balancing effect between pro‑inϐlammatory and anti‑inϐlammatory cytokine gene expressions by Gelsemium. Ultra‑diluted GS in homeopathic doses can effectively modulate the expression of cytokine genes in SARS‑CoV‑2‑induced cytokine imbalance. Further studies are desired to understand its utility in clinical practice through structured clinical trials.